Losartan protects against myocardial ischemia and reperfusion injury via vascular integrity preservation. Issue 7 (16th April 2019) - Li, Yong; Yao, Yufeng; Li, Jia; Chen, Qiuyun; Zhang, Lu; Wang, Qing K.
ABSTRACT: Vascular hyperpermeability caused by distorted endothelial cell‐cell junctions is associated with the no‐reflow phenomenon after opening of the occluded vessels in patients with coronary artery disease (CAD), the leading cause of death worldwide. Coronary no‐reflow is observed in ∼30% of CAD patients after percutaneous coronary stenting and is associated with a worse prognosis at follow‐up and a higher incidence of death. However, limited tools are available to control vascular hyperpermeability and no‐reflow. Losartan, an angiotensin II (Ang II) receptor blocker acting on the Ang II type‐1 receptor (AT1R) subtype, is a prescription drug for treating hypertension. Here we show that in a murine model of ischemia and reperfusion (I/R), losartan blocked vascular hyperpermeability and decreased infarct size, hemorrhages, edema, and inflammation. Mechanistically, losartan‐mediated inhibition of vascular hyperpermeability is mediated by the inhibition of phosphorylation of Src and vascular endothelial Cadherin (VE‐cadherin), which increases VEGF receptor 2 (VEGFR2)–Src‐VE‐cadherin complex formation, resulting in increased cell surface VE‐cadherin and inhibition of vascular hyperpermeability. On the other hand, hypoxia and reoxygenation increased the phosphorylation levels of Src and VE‐cadherin and reduced the formation of the VEGFR2‐Src–VE‐cadherin complex, which led to reduced cell surface VE‐cadherin and increased vascular hyperpermeability; all were inhibited by losartan. These data suggest that losartan may be used for blocking vascular hyperpermeability associated with I/R.—Li, Y., Yao, Y., Li, J., Chen, Q., Zhang, L., Wang, Q. K. Losartan protects against myocardial ischemia and reperfusion injury via vascular integrity preservation. FASEB J. 33, 8555–8564 (2019). www.fasebj.org